This I Believe - Roosevelt, Theodore (Tufts Archival Research Center, 2006)
Theodore Roosevelt III describes what he believes was an unusual family life growing up--his father ensured he spent time with the children--and describes his own belief in and appreciation for the support of his wife and the value of a strong home life.